Virtual design for package boiler - Ramasamy Muthusamy Senthil (2008)
This project discusses the successful development of a virtual and collaborative design software, Vdesign, for information communications within a company and external sites. Vdesign is capable of facilitating designing activities, sharing fdes (2 or 3 dimensional drawings) and information as well as discuss issues over the Intranet, Extranet and Internet.